Allosteric inhibition abrogates dysregulated LFA-1 activation: Structural insight into mechanisms of diminished immunologic disease. (April 2018) - Abdullahi, Maryam; Olotu, Fisayo A.; Soliman, Mahmoud E.
Graphical abstract: Highlights: Mechanistic events linked to integrin inactivation is vital for inhibition. Lifitegrast favours low affinity conformation of Lymphocyte function antigen-1. Lifitegrast is a potent allosteric inhibitor of Lymphocyte function antigen-1. Abstract: Lymphocyte Function Associated antigen-1(LFA-1) has been implicated severely in the pathophysiology of inflammatory and autoimmune diseases. Its active and inactive conformations correlate with its diseased and non-diseased state respectively. This is determined by its degree of affinity for its intrinsic ligand (ICAM) at the active site and accompanying synergistic coordination at the α7 helix. This potentiates the role of inhibitors in disrupting this interaction allosterically. Herein, we present a first account of the structural dynamics which characterizes the inhibitory effect of a novel LFA-1 antagonist, Lifitegrast (SAR1118), upon binding to the I-domain allosteric site (IDAS) using molecular dynamics simulation. Findings from this study revealed that the inhibitor stabilized the closed conformation and reversed the open conformation to a low ICAM-affinity state (closed) as evidenced by the upward movement of the α7 helix and corresponding transitions at the active site. This in both cases favors the formation of the non-disease inactive form. Upon allosteric modulation, the inhibitor significantly restored protein stability, enhanced compactness and decreased residual fluctuation as crucial to its potency in the amelioration of immunological and inflammatory diseases which agrees with experimental studies. These findings could therefore serve as the basis for the exploration of the allosteric domain and its active site affinity modulation to aid the design of more specific and selective inhibitors.